An Overview on the Manhole Edge Computing (International Journal of Innovative Research in Computer Science & Technology, 2021)
One of the most important basic platforms  in a smart city for preventing recurrent manhole cover  accidents is an intelligent manhole cover management  system. Manhole cover removal, loss, and injury endangers  people's safety, which is contrary to the aim of smart cities.  This article describes an intelligent manhole cover  management system (IMCS) for smart cities that is based  on edge computing. Each manhole cover has its own radio  frequency identification tag with tilt and vibration sensors,  and communication is done through a narrow-band Internet  of things. Meanwhile, based on the collected data, edge  computing servers communicate with appropriate  management employees through mobile devices. The  effectiveness of the proposed IMCS was shown in a  demonstration application in Hangzhou's Xiasha District. It  halved the repair time, possibly improving the safety of  both humans and manhole covers.
Keywords: IOT; GSM; Mobile device; Power Supply; Vehicle